Cost minimisation analyses of birth care in low-risk women in Norway: a comparison between planned home birth and birth in a standard obstetric unit - Pål Joranger; Anette Schaumburg Huitfeldt; Stine Bernitz; Ellen Blix (BMC, 2024)
Abstract Background Evidence exists that planned home births for low-risk women in settings in which they have access to hospital transfer if needed are safe. The costs of planned home births, compared to low-risk births in obstetric units, are not clear. The aim of this study was to compare costs associated with hospital births versus home births under different home birth organizations. Methods We performed a cost minimisation analysis (CMA) based on decision-analytic modelling while assuming that health outcomes were not affected by place of birth. Estimations of resource use were mainly based on three existing Norwegian datasets: (1) women with planned home births (n = 354), (2) women with planned home births (n = 482) of which 63 were transferred to a hospital, and (3) women with planned births in a hospital (n = 1550). Results Planned home birth costs 45.9% (credibility interval [CrI] 39.1-54.2) of a low-risk birth at a hospital. For planned home birth, the birth was the costliest activity (32.1%). The costs for planned home birth were estimated to be €1872 (CrI 1694-2071) and included hospitalisations for some. Costs for only those with actual home birth was €1353 (CrI 1244-1469). Costs of a birth, including possible birth-related complications, in low-risk women in a hospital was €4077 (CrI 3575-4615). When including the costs of being on call for one woman at a time, a planned home birth costs €5,531 (CrI 5,171-5,906), which is 135.7% (CrI 117.7-156.8) of low-risk births at a hospital. When organizing midwives in the on call teams for multiple women at a time, a planned home birth costs € 2,842 (CrI 2,647-3,053), which is 69.7% (CrI 60.3-80.9) of a low-risk birth in a hospital. Conclusions Home birth can be cost-effective if the midwives who facilitate home births are organised into larger groups, or they work for hospitals that also facilitate home births. A model in which midwives work separately or in pairs to assist with a home birth and are on call for one birth at a time may not be cost-effective.